ANALYSIS OF INNOVATIONS AND PROSPECTS IN MODERN PEDAGOGY - Khilola Ruzmetova; Guzal Kurbonova; Anna Agaronian; Uguldzhan Abdullaeva; Nodirbek Muradov (The Bioscan, 2024)
Pedagogy today is a fundamental science on issues of training and education. Without skillful use of theoretical and methodological ideas of pedagogy, it is impossible to complete educational reform, improve the activities of educational institutions. In turn, the development of pedagogy is influenced by ideology, politics and the objective needs of society in the upbringing and education of youth.